A study on the functional outcome of closed reduction and K-wire fixation in the treatment of extra-articular distal radius fractures - Kaushik SB,; Jeevan Pereira,; Shenoy RM, (Asian Journal of Medical Sciences, 2024)
Background: Fractures of the distal end of the radius are among the most common skeletal injuries with diverse treatment options. There is no clear consensus regarding the functional outcomes of the diverse treatment options. Aims and Objectives: The aim of the study was to evaluate functional outcomes in distal radius fractures treated with closed reduction and K-wire fixation. Materials and Methods: Fifty-seven patients (26 males and 31 females) with different types of distal radial fractures were treated. Closed reduction and K-wire fixation were performed under axillary block or general anesthesia. Functional outcomes were evaluated using the Mayo Wrist Scoring System. Results: According to the Mayo score, 50.9% (n=29) of our patients had good outcomes, 36.8% (n=21) had fair outcomes, and 12.3% (n=7) had satisfactory outcomes. Conclusions: Closed reduction and Kirschner wire fixation are inexpensive procedures that provide anatomical reduction, fracture fixation, and maintenance of reduction with an adequate method of immobilization.